Correction to: Synergistic effect of the verapamil and amphotericin B against Cryptococcus neoformans (Folia Microbiologica, (2023), 68, 6, (999-1004), 10.1007/s12223-023-01104-5) - Pereira, Thaís C. [UNESP]; do Carmo, Paulo H. F. [UNESP]; de Menezes, Raquel T. [UNESP]; de Oliveira, Haroldo C.; de Oliveira, Luciane D. [UNESP]; Junqueira, Juliana C. [UNESP]; Scorzoni, Liliana [UNESP] (Springer Nature, 2024)
In the article Synergistic effect of the verapamil and amphotericin B against Cryptococcus neoformans (https://doi.org/10.1007/s12223-023-01104-5) written by Thaís C. Pereira, Paulo H. F. do Carmo, Raquel T. de Menezes, Haroldo C. de Oliveira, Luciane D. de Oliveira, Juliana C. Junqueira and, Liliana Scorzoni, the authors, Haroldo C. de Oliveira and Liliana Scorzoni would like to correct the acknowledgment section, including an acknowledgment to Dr. Arturo Casadevall for providing the anti-GXM antibody 18B7 to our experiment to detect GXM in the supernatant of C. neoformans cultures. We thank Dr. Marcio L. Rodrigues (Instituto Carlos Chagas, Fiocruz, Curitiba-PR, Brazil) for the support in GXM evaluation, Dr. Arturo Casadevall (Johns Hopkins University, Baltimore, USA), for donating the anti-GXM antibody 18B7 and Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES – Brazil) for the scholarship support.